Формування принципу верховенства права Європейського Союзу - Юхимюк, О.; Дмитрук, С.; Iukhymiuk, O.; Dmytruk, S. (СНУ ім. Лесі Українки, 2018)
У статті проведено аналіз закріплення та легалізації принципу верховенства права Європейського Союзу як елемента складної правової системи Європейського Союзу. Принцип верховенства права Європейського Союзу був сформований в практиці Суду Європейського Союзу, але законодавчо не закріплений. Спроба закріпити принцип верховенства права ЄС була зроблена в проекті Конституції ЄС, яка зазнала невдачі. Хоч в Лісабонському договорі 2007 р. його не закріпили, він відображений в Директиві № 17, яка є додатком до договору. The article analyzes the consolidation and legalization of the principle of supremacy of European Union’ law as an element of a complex legal system of the European Union. Principle of supremacy of European Union’ law means advantage in applicationon of European Union’ law to the national law of states-members. This principle applies to all norms of national legislation of states-members of European Union, regardless of their hierarchy of sources of law. Principle of supremacy of European Union’ law was formed in practice of Court of justice of European Union, but legislatively not fixed. The attempt to consolidate the analyzed principle was made in the draft European Union constitution that failed. Although in the Lisbon Treaty of 2007 the principle of the supremacy of European Union’ law has not been consolidated, it is reflected in Directive No. 17, which is an annex to the above-mentioned treaty. The analyzed principle helps to resolve conflicts between the legal system of the European Union and the national legal systems of its members.
Formation of the Principle of Supremacy of European Union’ Law
Keywords: принципи права; принцип верховенства права Європейського Союзу; Суд справедливості Європейського Союзу; the principles of law; the principle of the rule of law of the European Union; the Court of Justice of the European Union